Presumptive Cycad Toxicosis in a Dog. Clinical and Magnetic Resonance Imaging Findings: A Case Report - Maeso, Christian; Morales, Carles; Obrador, Rafael; Abarca, Eva; Carrera, Inés (Frontiers in Veterinary Science, 2020)
Cases of cycad toxicosis have been described in dogs that have presented with gastrointestinal, hematologic, hepatic, neurological, and carcinogenic signs. This case report describes brain magnetic resonance imaging (MRI) lesions in a dog with gastrointestinal and neurological signs secondary to cycad toxicosis. A 5-year-old neutered female Jack Russell Terrier presented with a 2-day history of gastroenteric signs, progressive generalized tremors, and altered mentation after possible ingestion of Cycad revoluta. Neurologic examinations revealed disorientation, a wide-based stance, severe spasticity of the four limbs, intention tremors, severe cerebellar ataxia, decreased postural reactions in all four limbs, and intermittent decreased menace response in both eyes; all of which are consistent with a multifocal intracranial disorder involving the forebrain and cerebellum. A brain MRI showed diffuse/ill-defined, intra-axial bilateral and symmetrical changes, predominantly affecting the white matter of the cerebral hemispheres, thalamus, hippocampus, and cerebellum. A presumptive diagnosis of toxic-metabolic encephalopathy was made. Medical management of the clinical signs was performed, and the dog was discharged 7 days after presentation with no neurological abnormalities. Two and eight weeks later, complete blood count (CBC), chemistry, electrolytes and eight weeks later brain MRI were performed, revealing no abnormalities. To the best of the authors´ knowledge, this is the first case report describing lesions detected by brain MRI secondary to cycad toxicosis, as well as a complete resolution of brain lesions on a follow-up MRI 8 weeks later.